Impact of Social Media on Fashion Trends and Consumer Behavior in Kenya - Muturi, Henry (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to investigate the impact of social media on fashion trends and consumer behavior. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Social media democratizes fashion by offering diverse content, shaping trends and consumer behavior. Platforms like Instagram and TikTok facilitate trend dissemination and peer-to-peer recommendations. They also integrate commerce, transforming the shopping experience. Ultimately, social media is pivotal in driving real-time fashion trends and shaping consumer preferences. Unique Contribution to Theory, Practice and Policy: Social identity theory, diffusion of innovation theory & social learning theory may be used to anchor future studies on the impact of social media on fashion trends and consumer behavior. Fashion brands and marketers should leverage social media platforms to engage with consumers in meaningful ways, fostering community-building and co-creation of content. Policymakers should consider regulating the transparency and authenticity of sponsored content on social media platforms to mitigate the potential for deceptive marketing practices and protect consumers from misinformation.